2007
DOI: 10.1091/mbc.e06-05-0418
|View full text |Cite
|
Sign up to set email alerts
|

A Chemoattractant-mediated Gi-coupled Pathway Activates Adenylyl Cyclase in Human Neutrophils

Abstract: Neutrophils and Dictyostelium use conserved signal transduction pathways to decipher chemoattractant gradients and migrate directionally. In both cell types, addition of chemoattractants stimulates the production of cAMP, which has been suggested to regulate chemotaxis. We set out to define the mechanism by which chemoattractants increase cAMP levels in human neutrophils. We show that chemoattractants elicit a rapid and transient activation of adenylyl cyclase (AC). This activation is sensitive to pertussis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 60 publications
1
36
0
1
Order By: Relevance
“…Cell exposure to forskolin, an adenylyl cyclase activator used as a positive control, led to a significant increase in cAMP concentrations in human neutrophils (Fig. 1C) within the range previously described (39). Taken together, these data demonstrate that resting human neutrophils and HUVECs express the a2A and the a2B adrenergic receptor, respectively.…”
Section: Human Neutrophils and Huvecs Express A2-adrenoceptorssupporting
confidence: 85%
“…Cell exposure to forskolin, an adenylyl cyclase activator used as a positive control, led to a significant increase in cAMP concentrations in human neutrophils (Fig. 1C) within the range previously described (39). Taken together, these data demonstrate that resting human neutrophils and HUVECs express the a2A and the a2B adrenergic receptor, respectively.…”
Section: Human Neutrophils and Huvecs Express A2-adrenoceptorssupporting
confidence: 85%
“…Perhaps the isoforms of adenylyl cyclase expressed in these cells are not subject to inhibition by G i , as has been demonstrated for neutrophils (Mahadeo et al, 2007). HL-60 cells gain a neutrophil phenotype upon differentiation and, therefore, are likely to reflect receptorpromoted signaling responses that are characteristic of neutrophils.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have established that the addition of chemoattractants to neutrophils leads to a small and temporary increase in the production of cAMP (43)(44)(45). We and others have reported that increased intracellular cAMP levels are associated with the inhibition of multiple intracellular activities, including the respiratory burst and the degranulation of neutrophils (24,46).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of FPR1 elicits multiple signaling pathways that trigger the human inflammatory responses. Phospholipase C catalyzes the conversion of phosphoinositol 4,5-biphosphate to inositol 1,4,5-triphosphate to cause the rapid release of Ca 2+ (45,47,48). In addition to the increase in [Ca 2+ ] i , the activation of PI3K/AKT signaling, as well as the ERK1/2 and p38 MAPK cascades, is mediated by the interactions between fMLF and FPR1 for multiple intracellular activities (49).…”
Section: Discussionmentioning
confidence: 99%